Development of an HPLC Method for Absolute Quantification and QAMS of Flavonoids Components in Psoralea corylifolia L. (26th October 2015) - Yan, Cuiping; Wu, Yu; Weng, Zebin; Gao, Qianqian; Yang, Guangming; Chen, Zhipeng; Cai, Baochang; Li, Weidong
Abstract : The seeds of Psoralea corylifolia L. (Fabaceae) are a commonly used medicinal herb in eastern Asia with many beneficial effects in clinical therapies. In this study, a simple, sensitive, precise, and specific reverse phase high-performance liquid chromatography (HPLC) method was established for quantification of 9 flavonoids in P. corylifolia, including isobavachin, neobavaisoflavone, bavachin, corylin, bavachalcone, bavachinin, isobavachalcone, corylifol A, and 4′-O-methylbavachalcone. Based on this method, a quantitative analysis of multicomponents by single marker (QAMS) was carried out, and the relative correction factors (RCFs) were calculated for determining the contents of other flavonoids. The accuracy of QAMS method was verified by comparing with the results of external standard method, as well as the feasibility and adaptability of the method applied on quality control of P. corylifolia . The 9 compounds were baseline separated in 60 min with a good linearity of regression coefficient( R 2 ) over 0.9991. The accuracies of QAMS were between 92.89% and 109.5%. The RSD values off in different injection volume were between 2.3% and 3.6%. The results obtained from QAMS suggested that it was a convenient and accurate method to determine multicomponents especially when some authentic standard substances were unavailable. It can be used to control the quality of P. corylifolia .